KULIAH DI JURUSAN ENTREPRENEURSHIP: LANGKAH STRATEGIS BAGI CALON PENGUSAHA MUDA - Rony Nur Triwibowo; Asharryadi Noegroho; Indra Rachmawati; Lia Ernawati (Aspirasi Masyarakat, 2024)
This community service activity aims to increase the motivation of Al-Irsyad Cilacap High School students in choosing entrepreneurship as their career choice. The background of this activity is the low interest of students in entrepreneurship due to a lack of understanding of career opportunities and benefits in this field. In addition, there is an assumption that entrepreneurship is a high-risk field and requires large capital, thus reducing students' interest in pursuing a career as an entrepreneur. Through a series of presentations and interactive discussions, students are introduced to the basic concepts of entrepreneurship, the importance of innovation in business, and the opportunities and challenges faced by entrepreneurs. The results of this activity showed a significant increase in students' interest and understanding of entrepreneurship. Surveys conducted before and after the activity showed a 30% increase in students' interest in continuing their studies in entrepreneurship. In addition, students also showed an increased understanding of the role of entrepreneurship in creating jobs and reducing unemployment. This activity succeeded in providing inspiration and motivation to students to pursue a career in entrepreneurship as prospective young entrepreneurs, as well as equipping them with the knowledge and skills needed to succeed in the future. It is hoped that similar activities can continue to be carried out to support the development of student potential and create a young generation that is ready to face the challenges of the world of work.